Production and characterization of yeast extracts produced by Saccharomyces cerevisiae, Saccharomyces boulardii and Kluyveromyces marxianus - Demirgul, Furkan; Simsek, Omer; Bozkurt, Fatih; Dertli, Enes; Sagdic, Osman (TAYLOR & FRANCIS INC, 2022)
In recent years, prejudice in society against monosodium glutamate (MSG) has directed food manufacturers to alternative sources. Yeast extracts are considered as natural due to the production process and stand out due to their nutritional properties as well as giving a flavor similar to MSG. In this study, chemical, functional and flavor properties of yeast extract powders produced from Saccharomyces cerevisiae TGM10, Saccharomyces boulardii S11 and Kluyveromyces marxianus TGM66 were evaluated. Results revealed that the most protein-rich sample was S. cerevisiae TGM10 extract (69.17%), followed by S. boulardii S11 (66.16%) and K. marxianus TGM66 (62.42%) extracts, respectively and S. cerevisiae TGM10 extract was also the richest yeast extract for essential amino acids. Additionally, flavor-enhancing amino acids such as glutamic acid, aspartic acid, alanine and glycine were dominant in S. cerevisiae TGM10 extract (47.41 g/100 g protein). Sensorial evaluation of yeast extracts demonstrated that salty taste, umami taste and meaty flavor scores of yeast extracts were lower than MSG whereas for fruity flavor, yeast extracts had the highest scores. These findings revealed the potential of three yeast strains to produce yeast extracts in order to increase the nutritional value and flavor of foods.
Keywords: Amino acids; Kluyveromyces marxianus; Saccharomyces boulardii; Saccharomyces cerevisiae; volatile compounds; yeast extract; SPENT BREWERS-YEAST; EMULSIFYING PROPERTIES; BAKERS-YEAST; PROTEIN; AUTOLYSIS; OPTIMIZATION; COMPONENTS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology